Experiencing : - Fiske-Rusciano, Roberta (McGraw-Hill, 2005)
This book is divided into three main division: "Identity", "Power" and "Change". It is guide for students in the thoughtful exploration of the issues that sorround personal and insitutionalized bigotry.